2017
DOI: 10.3892/or.2017.5361
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glia maturation factor γ is associated with colorectal cancer metastasis and its downregulation suppresses colorectal cancer cell migration and invasion in vitro

Abstract: Glia maturation factor γ (GMFG) functions to reorganize the actin cytoskeleton and appears to play a causative role in cell migration and adherence. The present study assessed GMFG expression in colorectal cancer cells and tissue specimens and then explored the role of GMFG in colorectal cancer progression in vitro. GMFG protein was highly expressed in colorectal cancer tissues and a metastatic colon cancer cell line. Knockdown of GMFG expression using GMFG siRNA or anti-GMFG antibody decreased the capacity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…We found that 30 of these genes which included Nckap1l, Ncf1, Pla2g15, Unc93b1, Lrrc33, Rgs10, Gmfg, Rbm25, C3ar1, Ccdc88b, Fam105a, Gng11, Phc1, Rasa4, Dag1, Tyrobp, Tmsb4x, Cfp, Prkd1, Gp49a, Trem2, C1qc, Lyz2, Igfbp7, Rab30, Cxcl16, Egfl7, Ube2r2, Pltp, and Cfb, showed a relation with cancer. Wang and colleagues first assessed GMFG expression in colorectal cancer cell lines and tissue specimens and found the targeting of GMFG expression may suppress colorectal cancer progression [ 64 ]. It has been reported that CCDC88B has a critical function in colon inflammation and the pathogenesis of IBD [ 65 ], and a previous study proved that patients with IBD have a higher probability of developing colorectal cancer than other people [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that 30 of these genes which included Nckap1l, Ncf1, Pla2g15, Unc93b1, Lrrc33, Rgs10, Gmfg, Rbm25, C3ar1, Ccdc88b, Fam105a, Gng11, Phc1, Rasa4, Dag1, Tyrobp, Tmsb4x, Cfp, Prkd1, Gp49a, Trem2, C1qc, Lyz2, Igfbp7, Rab30, Cxcl16, Egfl7, Ube2r2, Pltp, and Cfb, showed a relation with cancer. Wang and colleagues first assessed GMFG expression in colorectal cancer cell lines and tissue specimens and found the targeting of GMFG expression may suppress colorectal cancer progression [ 64 ]. It has been reported that CCDC88B has a critical function in colon inflammation and the pathogenesis of IBD [ 65 ], and a previous study proved that patients with IBD have a higher probability of developing colorectal cancer than other people [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive migration and invasion of tumor cells is recognized as the first step of neoplasm metastasis. 19 , 20 The effect of decreased Nodal expression on cell migration and invasion was determined by transwell assay. Our results demonstrated that downregulation of Nodal significantly inhibited the cell migration and invasion capabilities of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that expression of GMFG was able to affect invasion and migration of ovarian cancer, and was correlate with survival rate of ovarian cancer (18,19). Wang et al also indicated that expression of GMFG was related to colorectal cancer metastasis (20). GMFG protein can regulate cytoskeleton reorganization of actin in microvascular endothelial and ovarian cancer cells, which was clearly an essential factor of many cellular processes including cytokinesis, endocytosis and chemotaxis, and affected the angiogenic sprouting in zebra fish (21)(22)(23).…”
Section: Discussionmentioning
confidence: 95%